Experimental study of transcranial pulsed current stimulation on relieving athlete’s mental fatigue - Shen, Yangyang; Liu, Jian; Zhang, Xinming; Wu, Qingchang; Lou, Hu (Frontiers in Psychology, 2022)
Objective To explore the effect of independently developed transcranial pulsed current stimulation (tPCS) on alleviating athlete’s mental fatigue. Methods A total of 60 college athletes were randomly divided into the active stimulation group (current intensity:1.5 mA, lasting for 15 min) and the sham stimulation group. Subjective questionnaires, behavior test, and functional near-infrared spectroscopy (fNIRS) test were conducted before and after the experiment. Two-way ANOVA with repeated measures was used to compare the differences in mental fatigue indexes before and after the two experimental conditions. Results After 7 days of exercise training, there was a significant difference in the main effect of the time factor in all indexes of the two groups (p < 0.05). The scores of rated perceived exertion (RPE) scale, positive and negative affect schedule (PANAS), critical flicker frequency (CFF), and reaction time (RT), in the tPCS treatment group, were better than those in the sham stimulation group (p < 0.05). After 7 days of exercise training, all the subjects had different degrees of athlete’s mental fatigue; the subjects in the active stimulation group have a good evaluation of the tPCS developed by the research group without adverse actions. Conclusion tPCS intervention can improve emotional state, reduce the subjective evaluation of fatigue, improve behavioral levels such as attention and reaction time and increase cerebral prefrontal blood flow and oxygen supply.